SAT0490 Poor Long-Term Adherence To Secondary Penicillin Prophylaxis among Pediatric Patients with Rheumatic Fever. (15th July 2016) - Amarilyo, G.; Chodick, G.; Somekh, I.; Zalcman, J.; Harel, L.
Abstract : Background: Recurrent episodes of acute rheumatic fever (RF) may contribute to the development or worsening of rheumatic heart disease (RHD) and was estimated to occur in 50–70% of RF patients prior to the introduction of penicillin. Meta-analyses from the United States showed that secondary penicillin prophylaxis (SPP) may reduce the incidence of RHD. Moreover, SPP using monthly Intra muscular (IM) Benzathine Penicillin was more effective in prevention of RF recurrences than daily oral SPP. Objectives: We aimed to evaluate the long-term adherence to SPP in RF patients using real-life data. Methods: The study population included children up to 18 years old in Maccabi Healthcare Services (MHS), a 2-million member health organization in Israel, who were diagnosed with acute RF between 1/1996 to 5/2015 and were dispensed at least one monthly pack of penicillin (either in oral or IM form). Treatment persistence was defined as continuation of drug use for the entire duration of therapy or until age 18, whichever occurred first. Adherence to treatment refers to the extent of drug use during the period of persistence, expressed as mean proportion of days covered (PDC). This was calculated by dividing the quantity of penicillin dispensed by the total time span between index date and age 18, leaving MHS, or 31 April 2015, whichever occurred first. Results: A total of 842 RF patients were identified. Mean (SD) ages at diagnosis among patients on oral (n=734) and IM (n=108) initial therapy were 8.6y (3.7y) and 10.9y (3.2y), respectively. The median PDC for the treatment regimens were oral: 8% [interquartile range (IQR) 2–33%] and IM: 10% (IQR 3–28%). Overall, days covered with SPP (figure 1 ) decreased exponentially from 103 days in the first year of therapy to 20 days in the 10th year. Conclusions: Adherence and persistence to secondary penicillin prophylaxis among Israeli children diagnosed with RF is poor. Although less effective, oral SPP was the preferred regimen. Intervention plans to increase adherence and persistence to SPP must be implemented in countries where RF still exists. Disclosure of Interest: None declared